POLITICAL PARTY BRANDING AND MEDIA CAPITALISM IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Nugraha, Aat Ruchiat; Sjoraida , Diah Fatma; Karya Guna , Bucky Wibawa (Journal of Jabar Economic Society Networking Forum, 2024)
The Industrial Revolution 4.0 has changed the way political parties build and maintain their brands, with digital and social media becoming the main tools in political communication strategies. Media capitalism, characterized by the concentration of media ownership in the hands of large conglomerates, influences the political landscape by reducing the diversity of perspectives in reporting and giving rise to significant bias. Media controlled by capitalist interests tend to provide favorable coverage to political parties with ties or affiliations with media owners, influencing voter perceptions and election results. Additionally, social media algorithms designed to maximize engagement and advertising revenue often amplify controversial and emotional content, exacerbating political polarization and spreading misinformation. Fake information that spreads rapidly through social media platforms disrupts the democratic process and undermines the integrity of elections. To overcome the negative impacts of media capitalism, efforts are needed to maintain media independence and integrity through support for investigative journalism and independent media, as well as stricter and more transparent regulations to reduce the concentration of media ownership. Media education is also important for increasing media literacy among the public, helping voters recognize false information and understand media bias. Collaboration between government, the media industry, non-governmental organizations and civil society is needed to create a healthy and sustainable media ecosystem, where digital technology is used to strengthen democratic processes.